Kenaikan harga beras yang terjadi pada tahun 2024 - Hidayatullah, Rengga Aditya (Maliki Interdisciplinary Journal, 2024)
The increase in rice prices among Indonesian people in early 2024 has had various significant impacts, including difficulties for consumers in meeting their basic needs. Based on an analysis of the factors that caused the price increase, including crop failure due to flooding, distribution of social assistance, unstable climate, increased production costs, and other factors, it appears that the demand for rice tends to be inelastic. Apart from that, the scarcity of rice also resulted in a market that was initially perfect starting to turn into a monopoly market. To overcome this problem, the government has taken steps, such as maintaining rice stocks through Perum Bulog, implementing the Cheap Food Movement, and distributing social assistance to the community.